Soluble CD163 is produced by monocyte-derived and alveolar macrophages, and is not associated with the severity of idiopathic pulmonary fibrosis. Issue 3 (April 2022) - Chauvin, Pierre; Morzadec, Claudie; de Latour, Bertrand; Llamas-Gutierrez, Francisco; Luque-Paz, David; Jouneau, Stéphane; Vernhet, Laurent
The soluble form of the membrane hemoglobin scavenger receptor CD163 (sCD163), released by shedding, is a strong marker for macrophage activation. Serum sCD163 levels rise in several acute inflammatory states and some fibrosing diseases. Monocyte-derived macrophages (MoDM) differentiated by macrophage colony-stimulating factor (M-MoDM) contribute to the pathophysiology of idiopathic pulmonary fibrosis (IPF), an irreversible and rapidly fatal interstitial lung disease. Since M-MoDM express high membrane CD163 levels, we thus postulated that sCD163 could be a relevant biomarker for macrophage activation in IPF. We found that M-MoDM constitutively released higher amounts of sCD163 (49.5 ± 24.5 ng/ml) than monocytes (0.45 ± 0.32 ng/ml) or MoDM differentiated with granulocyte macrophage-stimulating factor (2.24 ± 0.98 ng/ml). The basal production of sCD163 by M-MoDM was increased following stimulation with lipopolysaccharide (123.4 ± 54.9 ng/ml) or ATP (168.9 ± 41.8 ng/ml). The sCD163 release was controlled by metalloproteases but not through ADAM17 activation. Moreover, CD163-positive macrophages and sCD163 were detected in pulmonary tissues and alveolar fluids of Caucasian patients with IPF, respectively. IPF alveolar macrophages constitutively secreted sCD163 amounts (67.6 ± 44.6 ng/µg RNA) which were significantly higher than those released by alveolar macrophages isolated from controls (19.2 ± 7.6 ng/µg RNA) or patients with other interstitial lung disease (31.5 ± 16.6 ng/µg RNA). However, the concentrations of sCD163 in blood serum collected from 155 patients with IPF did not correlate with the severity of their disease. In conclusion, our results show that M-MoDM constituted a pertinent model to study the regulation of sCD163 production. Yet, serum sCD163 values could not provide a prognostic biomarker for IPF in our cohort.